2022
DOI: 10.28991/hef-sp2022-01-04
|View full text |Cite
|
Sign up to set email alerts
|

Acid Whey Valorization for Biotechnological Lactobionic Acid Bio-production

Abstract: The dairy industry is facing a problem associated with 1.6 billion tons of acid whey per year as a waste stream. The extended amount of acid whey has encouraged studies for novel approaches of acid whey utilization. The production of lactobionic acid (LBA) using dairy waste has been in rapid demand as an economically feasible and environmentally friendly approach. The composition of acid whey makes lactose conversion into LBA by Pseudomonas taetrolens complicated. Therefore, the aim of the current research was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Industrially, LBA is generally produced by chemical synthesis; however, recent research has focused on bioconversion methods due to their higher selectivity, specificity, and use of milder conditions (Chidar, 2022). This is evident in the number of studies examining the bioconversion of LBA from different whey streams published in 2022 alone (Chidar et al, 2022;Narala et al, 2022;Sarenkova et al, 2022;Wu et al, 2022). Chidar (2022) recently examined factors affecting the bioconversion of lactose and WP into LBA using combinations of different enzymes, as well as the assistance of novel methods such as ultrasonication, microwave, and mechano-milling activation.…”
Section: 12mentioning
confidence: 99%
See 1 more Smart Citation
“…Industrially, LBA is generally produced by chemical synthesis; however, recent research has focused on bioconversion methods due to their higher selectivity, specificity, and use of milder conditions (Chidar, 2022). This is evident in the number of studies examining the bioconversion of LBA from different whey streams published in 2022 alone (Chidar et al, 2022;Narala et al, 2022;Sarenkova et al, 2022;Wu et al, 2022). Chidar (2022) recently examined factors affecting the bioconversion of lactose and WP into LBA using combinations of different enzymes, as well as the assistance of novel methods such as ultrasonication, microwave, and mechano-milling activation.…”
Section: 12mentioning
confidence: 99%
“…Industrially, LBA is generally produced by chemical synthesis; however, recent research has focused on bioconversion methods due to their higher selectivity, specificity, and use of milder conditions (Chidar, 2022). This is evident in the number of studies examining the bioconversion of LBA from different whey streams published in 2022 alone (Chidar et al., 2022; Narala et al., 2022; Sarenkova et al., 2022; Wu et al., 2022).…”
Section: Indirect Applications (Lactose Derivative and Ingredients)mentioning
confidence: 99%
“…Mamuad et al (2019) suggested that the highest levels of total bacteria and Ruminococcus flavefaciens were produced by supplementation with 0.1% E. faecium SROD, while the highest levels of total fungi and Fibrobacter succinogenes were produced by supplementation with 1.0% E. faecium SROD. Another function of LAB, including Pseudomonas spp., was the production of Lactobionic Acid (LBA), which was utilized in the pharmaceutical, food, medical, cosmetic, and chemical sectors, for example, in the development of skincare and anti-aging products (Narala et al, 2022).…”
Section: Rumen Total Bacteria Cellulolytic Bacteria and Total Protozo...mentioning
confidence: 99%
“…The concept of the zero-waste economy advocates for utilizing waste as a raw material for novel food products, ingredients, and applications [5]. Figure 1 schematically illustrates the recovery of bioactive fractions through conventional and novel technologies and their consequent valorization as natural additives or active ingredients in various sectors [6], including food, cosmetics, and pharmaceuticals [7].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, due to the incomplete removal of solvents in downstream processes, the extracted phytochemicals may have adverse effects on human health, potentially impacting the quality of the extract (for example, losing the functionality of the desired compounds) and, consequentially, their applications. The use of green and food-grade solvents, which have lower affinities for their target compounds, requires longer extraction times, high-purity solvents, and heat treatments, resulting in the degradation of thermolabile phytochemicals [5][6][7]. Therefore, efforts have been directed toward developing more efficient, sustainable, and ecologically friendly extraction technologies, such as enzymeassisted extraction [8,9], supercritical fluid extraction, microwave-assisted extraction [10], and ultrasound-assisted extraction [11].…”
Section: Introductionmentioning
confidence: 99%